1994
DOI: 10.1002/j.1556-6676.1994.tb01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity, Femininity, and Hispanic Professional Women's Self‐Esteem and Self‐Acceptance

Abstract: The literature suggests that whereas women experience unique challenges with self‐esteem, Hispanic professional women experience an additional challenge of balancing majority culture values with a more family‐oriented ethnic identity. This study investigated differences in self‐esteem, self‐acceptance, masculinity, femininity, and locus of control among Hispanic professional women, non‐Hispanic professionals, scientists, college students, clients, and victims of domestic violence. Masculinity scores were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In addition, self-acceptance and self-esteem are conceptually similar (in that both include positive affect about oneself) and much of the previous research demonstrating an association between Affirmation & Belonging and psychological well-being has used self-esteem as a measure of well-being (Smith & Silva, 2011). However, despite their similarities, these two constructs are not equivalent and differentially relate to other psychosocial processes (Long, 1986;Long & Martinez, 1994). Our study is one of the few to explore how self-acceptance is related to ethnic Affirmation & Belonging and we found, consistent with Brittian, Umaña-Taylor, and Derlin's (2013) results, a positive relationship between these two variables; therefore, our finding extends previous research.…”
Section: Ei's Relation To Self-acceptancementioning
confidence: 99%
“…In addition, self-acceptance and self-esteem are conceptually similar (in that both include positive affect about oneself) and much of the previous research demonstrating an association between Affirmation & Belonging and psychological well-being has used self-esteem as a measure of well-being (Smith & Silva, 2011). However, despite their similarities, these two constructs are not equivalent and differentially relate to other psychosocial processes (Long, 1986;Long & Martinez, 1994). Our study is one of the few to explore how self-acceptance is related to ethnic Affirmation & Belonging and we found, consistent with Brittian, Umaña-Taylor, and Derlin's (2013) results, a positive relationship between these two variables; therefore, our finding extends previous research.…”
Section: Ei's Relation To Self-acceptancementioning
confidence: 99%
“…The self-acceptance literature continued along established lines. The validity of the self-other correlation continued to be studied (e.g., Hurley, 1989Hurley, , 1991Hurley, , 1993Hurley, Feintuch, & Mandell, 1991;Hurley & Rosenberg, 1990), as did the relationship of self-acceptance to a variety of variables, such as: psychopathology (Richter, Richter, Eisemann, & Seering, 1995), treatment outcomes (Lemberg, 1993;Weissman & Appleton, 1995), behavioral effects (Pufal-Struzik, 1998), height and intelligence (Rienzi, Scrams, & Uhles, 1992), culture and occupation (Long, 1991;Long, & Martinez, 1994), disability (Fukunishi, Koyama, & Tombimatsu, 1995;Smart & Smart, 1991), and quality of life (Rogers, 1995). Ryff (1995) included self-acceptance as one of six facets of well-being in her widely used well-being scales (see Measurement of Acceptance section below).…”
Section: Smentioning
confidence: 99%
“…In tapping general gender role orientations, the BSRI appears to avoid the conceptual bias of treating machismo as an exaggerated hypermasculine role, although empirically the utility of the BSRI for studying Hispanic populations may be limited. Specifically, the BSRI was initially developed in college student samples, and recent applications of the measure in Hispanic samples have largely relied on college students (de Leon, 1993) or samples of Hispanic professionals or scientists (Long & Martinez, 1994, 1997. One recent large-scale study of the BSRI among Hispanic, non-Hispanic White, and African American adults (Harris, 1994) found that the BSRI appeared valid among non-Hispanic Whites but less valid in the two minority groups.…”
Section: Empirical Approaches To Measuring Machismomentioning
confidence: 99%